Efforts to Improve Student Learning Outcomes at Mugoe Rayeuk Elementary School Using the Sharing Method and Audio Visual Media - Marlinda; Rusni (MANDAILING GLOBAL EDUKASIA, 2025)
This study aimed to explore the effectiveness of using sharing methods and audio-visual media to improve students’ learning outcomes in Islamic Education at SD Negeri Mugoe Rayeuk. A quasi-experimental design with a control group was used, involving 60 5th grade students, divided into an experimental group (n=30) and a control group (n=30). The experimental group participated in lessons that integrated sharing methods and audio-visual media, while the control group received conventional teaching methods. Data were collected through pre-test and post-test assessments to measure students’ learning outcomes, in addition to classroom observations to measure students’ engagement and participation. The results showed a significant improvement in the learning outcomes of the experimental group, with higher post-test scores compared to the control group. The experimental group also showed increased engagement and active participation during the lessons, especially through collaborative activities and the use of multimedia tools such as videos and animations, which helped clarify complex concepts and make learning more interactive. The sharing method encouraged collaboration, critical thinking, and peer learning, while audio-visual media enhanced comprehension by providing visual and audio representations of the content. In contrast, the control group, which followed the traditional method, showed only modest improvements in learning outcomes. The findings indicate that sharing methods and audio-visual media significantly increased students’ engagement, understanding, and retention of Islamic Education concepts, offering a more effective approach to improving academic performance. This study highlights the importance of adopting innovative and interactive teaching methods in the classroom and suggests further exploration of their application in various educational settings.